Balancing risks: Qualitative study of attitudes, motivations and intentions about attending for mammography during the COVID-19 pandemic. Issue 7 (November 2021) - Kirkegaard, Pia; Edwards, Adrian; Andersen, Berit
Aims: To explore attitudes, motivations and intentions about attending for mammography among women who cancelled or postponed breast cancer screening, which had remained open in Denmark during the COVID-19 pandemic. Methods: A telephone interview study was conducted at the end of April 2020. A qualitative, phenomenological approach was chosen to identify themes and concepts and a semi-structured interview guide was developed. The analysis was structured according to constructs from the theory of planned behaviour, including attitudes to breast cancer screening, norms and motivations to comply with breast cancer screening, perceived control and anticipated regret. Results: Interviews were carried out with 33 women aged 50–69 (mean 62) years. The women felt that screening was of secondary importance during the height of the pandemic and they felt low perceived control over transportation to the screening clinic and over the screening situation itself, where social distancing was impossible. They perceived messages from the authorities as conflicting regarding the request for social distancing and a lack of recommendations about using face masks at the screening clinic. Conclusions: Women who postponed or cancelled breast cancer screening during the COVID-19 pandemic felt that public recommendations appeared contradictory. Uncertainty about the 'new norm(al)' of COVID-19 made them stay at home, although the screening clinics remained open. The findings point to the importance of addressing perceived inconsistency between recommendations from the World Health Organization and the national management of these recommendations, and to secure univocal information from the authorities about the recommended use of healthcare services in a time of crisis.